2008
DOI: 10.1590/s0104-42302008000500014
|View full text |Cite
|
Sign up to set email alerts
|

Toxicidade da azatioprina na doença de Crohn: incidência, abordagem e evolução

Abstract: . A terapêutica medicamentosa, antes limitada aos corticosteróides, antibióticos e aminossalicilatos, inclui hoje os imunossupressores/imunomoduladores e terapêuticas bioló-gicas, sendo essas duas últimas classes empregadas cada vez mais freqüentemente entre nós, e muitas vezes capazes de recuperar pacientes antes considerados intratáveis 6 . Dentre os imunomoduladores, destacam-se os análogos da purina: a 6-mercaptopurina (6-MP) e seu precursor, a azatioprina (AZA) 7 . As principais indicações para o tratamen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Inflammatory bowel diseases (IBD) have in common chronic inflammation of the digestive tract, which may or may not have a cause or specific pathogen (5,7) . Its etiology is multifactorial and complex, it is believed to have genetic involvement, environmental, immune and intestinal microbiota (26,30) .…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory bowel diseases (IBD) have in common chronic inflammation of the digestive tract, which may or may not have a cause or specific pathogen (5,7) . Its etiology is multifactorial and complex, it is believed to have genetic involvement, environmental, immune and intestinal microbiota (26,30) .…”
Section: Introductionmentioning
confidence: 99%
“…(5) Leukopenia is a major long-term adverse effect of treatment with AZA and/or MSZ. (5,6,9) Colli et al (10) reported leukopenia in 36 out of 106 (34%) patients with IBD treated with AZA, with a mean time to onset of leukopenia of 35 months after initiation of treatment. Lémann et al (11) evaluated 87 patients with long-term IBD and found a prevalence of leukopenia of 24.5%.…”
Section: ❚ Discussionmentioning
confidence: 99%